08.20 Acpa fingerprinting in established rheumatoid arthritis. (1st March 2017) - Manca, Maria L; Alunno, Alessia; D'Amato, Claudia; Bistoni, Onelia; Puxeddu, Ilaria; Gerli, Roberto; Migliorini, Paola; Pratesi, Federico
Abstract : Background: Anti-citrullinated protein/peptide antibodies (ACPA) represent an important tool for the diagnosis of RA and the presence of multiple ACPA specificities is highly correlated with the evolution towards RA. 1 However, a limited amount of information is available on the predictive value of single specificities on disease manifestations and response to therapy in established RA The aim of the present work is to evaluate the diagnostic and prognostic value of the combined use of four well established citrullinated peptides as antigens for ACPA detection: VCP1 and VCP2 (derived from EBV proteins) and HCP1 and HCP2 (derived from histone H4). 2, 3 Materials and methods: Four hundred and forty-eight RA patients, followed in the Clinical Immunology Unit, University of Pisa, and in the Rheumatology Unit, University of Perugia, were recruited. RA patients were evaluated for systemic involvement, disease activity and severity, ongoing and past therapies. Anti-VCP1, -VCP2, -HCP1, -HCP2 were measured by home-made ELISA. Data were analysed by cluster analysis and principal component analysis. Results: Antibodies to VCP1 were detected in 52% of RA patients; anti-VCP2 in 59, 5%; anti-HCP1 in 57% and anti-HCP2 in 57, 5% Cluster analysis and principal component analysis identify two subpopulations, that differ for ACPA levels, RF positivity, lung involvement and higher use of biological therapy. Patients were also subdivided in 5 groups according to the number of anti-peptide antibodies (negative for any, positive for one, for two, for three, for four). Mean antibody level and RF positivity progressively increased from the first to the last group, as well as the frequency of lung involvement. Conclusions: ACPA are a family of antibodies with overlapping specificities. The results obtained with citrullinated peptides from EBV proteins and histone H4 suggest that fingerprinting of ACPA may be informative in established RA. A higher number of ACPA subtypes is predictive of lung involvement. Moreover, a broader ACPA repertoire also emerged as a feature of patients treated with biological therapy, thus probably affected by a more severe form of the disease. In conclusion, ACPA typing may be relevant for a better characterisation of some disease features in established RA. References: 1. Brink M, Hansson M, Mathsson L, et al . Multiplex analyses of antibodies against citrullinated peptides in individuals prior to development of rheumatoid arthritis. Arthritis Rheum. 2013;65(4):899–910 2. Panza F, Pratesi F, Valoriani D, et al . Immunoglobulin G subclass profile of anticitrullinated peptide antibodies specific for Epstein Barr virus-derived and histone-derived citrullinated peptides. J Rheumatol2014;41(2): 407–8. 3. Johansson L, Pratesi F, Brink M, et al . Antibodies directed against endogenous and exogenous citrullinated antigens pre-date the onset of rheumatoid arthritis. Arthritis Res Ther2016;18(1):127.